2022
DOI: 10.1007/s11023-022-09597-8
|View full text |Cite
|
Sign up to set email alerts
|

Minds and Machines Special Issue: Machine Learning: Prediction Without Explanation?

Abstract: design drugs to turn proteins off (or on)? How can we design proteins to perform new functions? Hence, there is a sense in which AlphaFold2's remarkable prediction comes without an explanation.This is an important sense, to be sure: AlphaFold2 does not explain how protein folding works. It seems to have somehow learned to bypass the step of explicitly modeling the biological mechanisms leading to the folded protein. Or maybe, there is an image of this mechanism somehow contained in the activation patterns of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Additionally, the retrospective nature of the study introduces potential sources of bias and limitations in data collection. Finally, ML models predict outcomes; however, they may not provide causal explanations or elucidate the underlying mechanisms of the predicted outcomes [36]. Although our study identified the risk factors associated with PPCs, it may not definitively establish causality or provide deep insights into the biological or physiological pathways involved when considering the present performance of our models.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, the retrospective nature of the study introduces potential sources of bias and limitations in data collection. Finally, ML models predict outcomes; however, they may not provide causal explanations or elucidate the underlying mechanisms of the predicted outcomes [36]. Although our study identified the risk factors associated with PPCs, it may not definitively establish causality or provide deep insights into the biological or physiological pathways involved when considering the present performance of our models.…”
Section: Discussionmentioning
confidence: 84%
“…Philosophers of science and scientists have taken up the central question of this debate by addressing the impact that the introduction of AI and machine learning is likely to have on the general character of scientific research (e.g. Pietsch, 2015;Canali, 2016;Coveney et al, 2016;Boon, 2020;Creel, 2020;Ourmazd, 2020;Boge and Poznic, 2021;López-Rubio and Ratti, 2021;Boge et al, 2022;Krenn et al, 2022;Duede, 2023;Andrews, 2023). The areas of genetics and molecular biology, which over the last few decades have become highly "data-centric" (Leonelli, 2016), seem particular prone to making the shift from a theory-or hypothesis-driven mode towards purely data-driven modes of research.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the general idea that indicates the existence of an inverse relationship between the interpretability of black-box models and the degree of precision reached by their predictions, although this relationship is not as simple as has been argued [28][29][30]. Recent studies on the challenge posed by the prediction/interpretability trade-off [28,29,31] and its explicit incorporation into hydrological modeling show that this is a hot topic and therefore transcendental in the discussion on the role that AI/ML/DL has in current hydrology and will continue to have in an increasingly digitized world [32][33][34].…”
Section: Introductionmentioning
confidence: 99%